UJI AKTIVITAS ANTIBAKTERI DAN ANTI-UV DARI EKSTRAK ETIL ASETAT ISOLAT JAMUR AFBK 5c YANG BERSIMBION DENGAN ASCIDIA Sigilina sp. DARI PERAIRAN PULAU BANGKA - Vesiy NM Tamburian; Deiske A Sumilat; Chatrien A Sinjal (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Bioactive compounds are toxic compounds produced by organisms for use in self-defense from a wide variety of predators residing in their environment. The aim of the study was to test antibacterial activity and prove the UV-preventing effectiveness of the AFBK 5c mushroom isolate ethyl acetate extract that is in conjunction with ascidia. This research was conducted for 1 month in two locations, namely for antibacterial testing conducted in the Laboratory of Molecular Biology and Marine Pharmaceuticals, FPIK and for anti-UV testing conducted at the Pharmaceutical Laboratory, FMIPA, UNSRAT. The results showed that; This type of fungus that has been extracted and used is a fungus with the isolate code AFBK 5c This mushroom is a fungus that is connected with sigilina sp type ascidia. The rough extract of ascidia symbiont mushrooms is obtained from the process of meseration using ethyl acetate, then antibacterial testing of S. aureus and E. coli test bacteria and showing results such as antibacterial activity with an average value in S. aureus 09.00 and E. coli 11.05 mm which shows that there is antibacterial activity of AFBK 5c fungus isolate against E. coli and S. aureus test bacteria so that it can be said that the symbiont fungus has the potential as an ingredient. manufacture of antibacterial drugs. Furthermore, anti-UV testing, and the results of testing anti-UV compounds using rough extracts of AFBK 5c fungus isolates can produce absorption in UV-B (Î» 290-320 nm) and UV-A (Î» 320-400 nm) so that it has the potential to be used as an anti-UV material.Keywords: Bioactive Compound, Ascidia, Meceration, Antibacterial, Anti-UV